2023
DOI: 10.1101/2023.06.21.23291564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and temporal clustering of anti-SARS-CoV-2 antibodies in Illinois household cats, 2021-2023

Chi Chen,
Mathias Martins,
Mohammed Nooruzzaman
et al.

Abstract: In this study, we evaluated the seroprevalence of SARS-CoV-2 antibodies in Illinois household cats from October 2021 to May 2023. Among 1,715 samples tested by serological assays, 244 samples (14%) tested positive. High-rate temporal, spatial, and space-time clusters of SARS-CoV-2 cases were assessed within 63 counties in Illinois. Three space-time clusters with higher than expected seroprevalence rates were identified in the northeastern, central-east, and southwest regions of Illinois, occurring between June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Experimental studies have, however, demonstrated cats' high susceptibility to SARS-CoV-2 infections and their potential to transmit the virus through close contact (11). Numerous studies have now reported seroprevalence of SARS-CoV-2 in domestic, shelter, and stray cats, yielding variable prevalence (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Despite now extensive global documentation, data on the seroprevalence of SARS-CoV-2 in U.S. domestic cats remains relatively scarce (23)(24)(25)(26)(27), especially during the early stages of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have, however, demonstrated cats' high susceptibility to SARS-CoV-2 infections and their potential to transmit the virus through close contact (11). Numerous studies have now reported seroprevalence of SARS-CoV-2 in domestic, shelter, and stray cats, yielding variable prevalence (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Despite now extensive global documentation, data on the seroprevalence of SARS-CoV-2 in U.S. domestic cats remains relatively scarce (23)(24)(25)(26)(27), especially during the early stages of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have now reported seroprevalence of SARS-CoV-2 in domestic, shelter, and stray cats, yielding variable prevalence (12–27). Despite now extensive global documentation, data on the seroprevalence of SARS-CoV-2 in U.S. domestic cats remains relatively scarce (23–27), especially during the early stages of the pandemic.…”
Section: Introductionmentioning
confidence: 99%